2014
DOI: 10.3390/ijerph110606375
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Civic Engagement for Men’s Health and Well Being in Norway—A Contribution to Public Health

Abstract: Objectives: Using the example of older men volunteering on teams that restore historic ships, this article examines the effects of volunteering on the well-being of older adults. We consider particularly how volunteering impacts levels of social engagement and explore how the men’s reminiscences as they bond with their fellows in highly skilled work helps integrate their life experiences. Methods: Data are based on 14 in-depth interviews with volunteers working on historic vessels in Norway. Self-rated health,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Many societies are continuing to age throughout the world. This makes civic participation and engagement an area of increasing importance, with many countries reexamining their approaches to dealing with aging [19,20]. While civic engagement is widely accepted and discussed as part of a conceptual framework for increasing social capital, little research has attempted to identify the phenomena related to the roles of social capital, social cohesion, and social engagement [21].…”
Section: Discussionmentioning
confidence: 99%
“…Many societies are continuing to age throughout the world. This makes civic participation and engagement an area of increasing importance, with many countries reexamining their approaches to dealing with aging [19,20]. While civic engagement is widely accepted and discussed as part of a conceptual framework for increasing social capital, little research has attempted to identify the phenomena related to the roles of social capital, social cohesion, and social engagement [21].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have focused on the consequences of social capital [1]. For example, social capital was found to have important effects on self-rated health (SRH), life satisfaction, depression, physical disease, and even mortality among older adults [1,2,3,4,5]. However, studies on the determinants of social capital among older populations are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on the individual level of social capital, which inheres in the density or closure of community social networks. This level of social capital is recognized as a key predictor of older populations’ health [1,2,3,4,5], which can be used by older adults to preserve social supportive resources and pursue their individual or collective interests [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, interpersonal trust and reciprocity are the strongest predictors of mental health factors like subjective wellbeing and life satisfaction in elderly people [25]. Building on this association, it has been found that social capital has significant effects on satisfaction of life, self-rated health condition, depression, physical disability, and death rate in the elderly population [26,27,28]. Regardless of methodological problems in social capital investigations, sociologists, policy makers, and international organizations like World Health Organization (WHO) and World Bank are highly interested in accepting and following the perspective that social capital is a major social determinant of cognitive health and contributes to mental wellbeing [29].…”
Section: Introductionmentioning
confidence: 99%